Evaluation of Outpatient Satisfaction with Pharmaceutical Services in the Era of National Health Insurance - Sari, Dewi Mardika; Dewi, Pramitha Esha Nirmala (International Journal Labs, 2023)
Background: The National Health Insurance (JKN) system has been able to improve the health status of the Indonesian people. However, efforts are still needed to accelerate the achievement of health indicators to catch up with other countries. Therefore, the researchers were interested in conducting research related to evaluating outpatient satisfaction with pharmaceutical services in the era of national health insurance at the PKU Muhammadiyah Gamping Hospital. Aim: The purpose of this study is to determine the profile of outpatient satisfaction and at what dimensional pointes outpatients are less satisfied with pharmaceutical services by using national health insurance at PKU Muhammadiyah Gamping hospital Method: This research is a non-experimental descriptive study with a cross sectional approach. Sampling is carried out prospectively by the purposive sampling method through questionnaires given to the target population. The number of statement items in this study is 29 satisfaction items and 29 expectations items in terms of 5 dimensions. Findings: The level of satisfaction of outpatients with pharmaceutical services in national health insurance users at PKU Muhammadiyah Gamping included the responsiveness dimension of 95.52%, the empathy dimension of 90.49%, the assurance dimension of 90.32%, the reliability dimension of 87.12%, and the tangible dimension of 86.40%. The result of the average value of the respondent's overall satisfaction level was 89.97%. Based on the average results of the value of the outpatient satisfaction level with the pharmaceutical services of national health insurance users at PKU Muhammadiyah Gamping Hospital, this value is included in the category of